Silamiut Teatret - Burkal, Ivan (Peripeti, 2019)
ærværende artikelsamling dels fordi kilderne til Silamiut Teaterets historie er sparsomme eller svært tilgængelige og dels for at belyse de vanskelige vilkår, som teateret fungerede under både økonomisk, lokalemæssigt og kulturpolitisk. The article “15 years with Silamiut” is included in this article collection partly because the sources of Silamiut Theatre’s history are sparse or difficult to access and partly to highlight the difficult conditions that the theater functioned in both economic, local and cultural policy